RESILIENT LINING MATERIALS FOR REMOVABLE DENTURES: TYPES, COMPOSITION AND TECHNOLOGY - Mariana Yankova; Bozhidar Yordanov; Mariana Dimova-Gabrovska; Nikolay Apostolov (Peytchinski Publishing, 2019)
For patients with removable dentures, requiring uniform distribution of masticatory forces, the use of elastic relining materials is indicated. They are classified with respect to various characteristics: chemical composition, technology, polymerisation process, final hardness - Shore A, etc. Two basic relining methods have been described in the scientific literature - direct (clinical), and indirect (laboratory). The combination of a laboratory method and a clinical procedure is named direct-indirect method. Direct and direct-indirect techniques are used for cold curing relining materials, while indirect techniques are used for heat curing elastic relining materials. The good knowledge of the types, techniques, processing and basic characteristics of elastic relining materials is an important factor for predictable results in the prosthetic treatment with removable dentures.